The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1365-2516.2009.02090.x
|View full text |Cite
|
Sign up to set email alerts
|

An open clinical study assessing the efficacy and safety of Factor IX Grifols®, a high‐purity Factor IX concentrate, in patients with severe haemophilia B

Abstract: Factor IX Grifols is a new high-purity plasma-derived FIX concentrate with two specific pathogen elimination steps. Until this study was performed, there were no detailed reports with an adequate number of patients on the clinical evaluation of this product. To determine the efficacy and safety of Factor IX Grifols for replacement therapy in previously treated patients with severe haemophilia B, this open, multicentre and non-randomized study included 25 male subjects over the age of 12 with severe haemophilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Our results support previous observations that virus-inactivated, human plasma-derived coagulation factor concentrates have an excellent safety profile [7][8][9][10][11][12]. Although only 36 patients received Beriate ® P during the 10-years of observation in this study, over 27 million IUs of the product were administered without transmission of viruses or the development of inhibitors in PTPs or the PUP.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results support previous observations that virus-inactivated, human plasma-derived coagulation factor concentrates have an excellent safety profile [7][8][9][10][11][12]. Although only 36 patients received Beriate ® P during the 10-years of observation in this study, over 27 million IUs of the product were administered without transmission of viruses or the development of inhibitors in PTPs or the PUP.…”
Section: Discussionsupporting
confidence: 89%
“…Another landmark study has demonstrated the safety of a pasteurized FVIII concentrate with regard to hepatitis in patients with haemophilia and no previous infusions [9]. Data from other study groups [11,12] have confirmed the safety of virus-inactivated plasmaderived coagulation factor concentrates.…”
Section: Discussionmentioning
confidence: 96%
“…In spite of this, a recent survey in Italy indicated that the two species of FIX are used in similar doses with similar outcome . There are no comparative studies on regular prophylaxis, but the investigated doses of rFIX tend to be higher than the originally studied and traditionally recommended ones of pdFIX. Based on PK calculations, the average dose needed with rFIX to obtain a 1 IU dL −1 (1%) trough level of FIX coagulant activity (FIX:C) has been estimated to be about twice that of pdFIX .…”
Section: Introductionmentioning
confidence: 95%
“…Information on 31 selected JA concerning 35 studies on HB and/or FIX is provided in Table . Overall 21 published studies (60.0%) were related to FIX, of which 17 (48.6%) were on safety, efficacy and/or pharmacokinetics of different FIX products , two studies on dosing , one on allergic reactions and one on use of FIX worldwide . HB was the focus of seven studies, of which three studies compared features of HA or FVII deficiency to HB, two studies on correlation between genotype and phenotype of HB , one registry on incidence of inhibitors, allergic and anaphylactic reactions and one study on the global prevalence of HB .…”
Section: Resultsmentioning
confidence: 99%